ABITUDINI ALIMENTARI ED EMERGENZA COVID-19 - Sebastiana Cipponeri, Valentina Maltese, Milena Mazzara, Rocco Aldo Lucido, Viviana Catania (Phenomena Journal)
The COVID-19 pandemic has significantly changed our habits, making us rediscover a different dimension from everyday life and forcing us, in no time, to change our life’s style. The situation of global emergency caused by diffusion of coronavirus disease (COVID-19) has had a huge psychological impact on individuals around the world. In particular, individuals with eating and weight disorders may experience greater emotional distress resulting in an increase in food psychopathology, exacerbation of mental health and difficulties in self-management. The aim of this research is to understand how the restrictive and isolation measures issued by governments to contrast and contain the spread of the SARS-CoV-2 virus are changing the eating habits and lifestyles of the population and what psychological consequences they entail. To this end, an anonymous survey has been planned and launched through the development of an online questionnaire to be administered to Italian adult population. The future intent is to be able to plan, taking into consideration the results obtained, interventions with an integrated Gestalt approach, which can contribute to achieving good food awareness and thus avoid an increase in all those psychopathologies that are favored or aggravated by behavioral habits incorrect, and to appropriately manage complications and critical issues in people suffering from eating and weight disorders.